Analysis of critical success factors of online international learning exchange of Korean school pupils with English‐speaking counterparts - Lee, Jong‐Yeon; Park, Sanghoon (British journal of educational technology, 2017)
This study identifies the factors influencing the success of online international learning exchange (ILE) among Korean school pupils who partnered with American and Australian pupils. In particular, it examined the effects of self‐efficacy (SE), exchange infrastructure (EI) and quality of exchange activities (QEA) on the students' learning satisfaction (LS), foreign language capability (FLC) and intercultural competence (IC). A survey was conducted with 236 Korean participants whose age was 10–15 years old and who had completed a one‐semester online ILE program. Structural equation modeling results revealed that SE, EI and QEA had a significant effect on the students' LS, FLC and IC, with considerable impact resulting from EI and QEA. The students' SE and EI further affected the improvement of their FLC, as mediated by QEA.